Leigos para o desenvolvimento: optimization of private donations through segmentation - Laureano, Raul M. S.; Vinhas da Silva, Rui; Pereira, Joana; Martins, Sandrina; Rodrigues, David (VI International Congress of Teaching Cases Related to Public and Nonprofit Marketing, 2014)
Leigos para o Desenvolvimento (LD) are a NGOD (Non-Governmental Organization for Development) whose financing derives from donations obtained in the wider community. In this context and with the purpose of optimizing resource allocation in donations collection and the maximization of revenue thereof, the current study aims to assess the relative effectiveness of segmentation tools in donations with that purpose in mind. In informing the process and strategy of donations and thus optimizing organizational revenue, we aim to confront the merits of intuitive and experiential solutions with those that result from empirical data gathered and statistical techniques applied to segmentation tools and techniques. We conclude that there exists no one segmentation solution for sorting out the problem, opting instead for claiming that each case should be treated as unique and evaluated on its own.